Effect of Ethylene Flow Rate and CVD Process Time on Diameter Distribution of MWCNTs - Shukrullah, S. (Taylor and Francis Inc., 2016)
To date, focus of the research activities in nanoscience was to control the chemical vapor deposition (CVD) growth of carbon nanotubes (CNTs) by changing the precursor pressure and process temperature. The effect of the precursor flow rate and process time on CNTs growth parameters has been overlooked in past studies and therefore is very little known. This study was focused on the optimization of the ethylene flow rate and CVD process time for CNTs growth over Fe2O3/Al2O3 catalyst in a fluidized bed chemical vapor deposition (FBCVD) reactor, operating at atmospheric pressure. Argon and hydrogen were considered as the carrier and supporting gases, respectively. Transmission electron microscope (TEM) and Scanning Electron Microscopy (SEM) were used to investigate the surface morphology, nanostructures, purity and yield of the grown CNTs. In-depth analysis revealed an increase in tube length, yield and the carbon concentration with ethylene flow rate in the range of 50â110sccm. However, an inverse relationship between flow rate and tube diameter distribution was predicted in the given work. The most favorable results were obtained at an ethylene flow rate of 100 sccm and a CVD process time of 60 minutes. The dense and homogeneous growth of relatively pure nanotubes of increased tube length and narrow diameter distribution, in the range of 20â25nm, was observed at optimized flow rate and process time. Â© Taylor & Francis Group, LLC.